TEORI WEWENANG DALAM PERIZINAN - Grace Sharon (Universitas Muhammadiyah Gresik, 2021)
Based on the provisions in the 1945 Constitution article 1 paragraph 3 which states the State of Indonesia is a state based on law, it brings the consequence that every government action must always be based on the law. From another point of view related to the development of the 21st century, the State is often said to have developed into a modern state. Whereas the state's tasks, which were initially very limited, have become increasingly widespread. This is due to the increasing needs of modern humans and especially those related to the interests of life together. Regarding the social dynamics that occur in the community, licensing arrangements are needed. A license as a one-sided government action is a stipulation arising from the strategies and techniques used by the Government to control or control various conditions or activities carried out by the community. In other words, licensing is very much needed as an instrument of community guidance. However, the author limits the scope of research on licensing only to the nature of the authority of the permit, so that the author's research in this article is done through a literature review.